Peningkatan pengetahuan tentang stimulasi, deteksi, dan intervensi dini tumbuh kembang (SDIDTK) - Niar Niar; Sumiyati Sumiyati; Masyitah Wahab (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Stimulation activities, early detection, early intervention, comprehensive and coordinated growth and development deviations in toddlers are carried out in the form of partnerships between families (parents, child caregivers and other family members), the community (cadres, community leaders, professional organizations, non-governmental organizations, and etc.) with professional staff (health, education and social), will improve the quality of early childhood growth and development and readiness to enter formal education. Objective: to increase parents' knowledge about stimulation, early intervention detection and growth and development in children so that they can have high awareness of controlling their children's growth and development through posyandu/puskesmas Method: Community Service Activities are carried out in the form of counseling about the importance of stimulation, early intervention detection and growth and development in children. Participants in Community Service Activities are all mothers who have babies in Rumpa village Result: From the results of the pre test analysis, most of the mothers did not know about the importance of stimulation, early intervention detection and growth and development, but after counseling, the post test results showed that almost all mothers understood the importance of stimulation, early intervention detection and growth and development in children. Conclusion: Outreach activities have been carried out on the importance of stimulation, early intervention detection and growth and development in children and this activity received a positive response from partners. It can be seen that during the counseling there was quite intensive communication interaction and increased knowledge and high awareness of controlling the growth and development of their children through posyandu /Public health center.